Assessment of Nahar biodiesel with TiO2 nanoparticles at increased fuel injection pressure of a diesel engine: Exergy, energy, statistical analysis - Akshay Jain; Bhaskor Jyoti Bora; Rakesh Kumar; Debabrata Barik; Nithin Kumar; Prabhu Paramasivam; Raman Kumar; Jasgurpreet Singh Chohan; Hasan Sh Majdi; Majed Alsubih; Saiful Islam; Chander Prakash; et al. (Case Studies in Thermal Engineering)
There is a need for sustainable diesel alternatives addressing fuel depletion, price instability, and environmental impact. A nanofuel is developed by blending Nahar Biodiesel with a concentration of 150 ppm of TiO2 nanoparticles. The nanofuel, named NBD-TNP, is tested for increased fuel injection pressure (FIP) and variable engine loads (EL). The prepared nanofuel is tested in a 3.5 kW diesel engine. Five FIPs (200–280 bar with 20 bar increments after each set of experiments) and five ELs (20–100 % with 20 % increment after each set of experiments) are used to display the results. NBD-TNP nanofuel showed positive outcomes with an increased FIP of 260 bar. The maximum exergetic efficiency of 40.11 %, the maximum value of BTE of 29.22 %, and the maximum NHRR is 67.86 J/°CA for the FIP of 260 bar for NBD-TNP nano fuel at 100 % engine load. The lowest CO and HC emission for the NBD-TNP nanofuel at FIP is 260 bar for all ELs. The statistically optimized value obtained from RSM analysis is 47.95 % of EL and 263.45 bar of FIP for optimum values of response variables. The study concludes that the NBD-TNP nanofuel is a promising alternative for diesel fuel at an FIP of 260 bar.